Relative Verity of Bordeline Sentence Относительность истины пограничного предложения Відносність істини граничного речення - L. A. Кatz (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The paper represents main ideas of my theory “Relative verity logic” (RVL), that combines advantages of two contrary approaches to vagueness (many-valued theory and supervaluationism). RVL allows the fruitful treatment of borderline cases while saving all the classical tautologies and inference rules; and on top of all this, it also avoids the trap of the sorites paradoxes. В статье излагаются основные идеи разработанной автором теории относительной истинности для расплывчатых предикатов «Relative verity logic» (RVL), которая представляет попытку соединить преимущества двух противоположных подходов к проблеме расплывчатости (многозначного и сверхоценочного). RVL предлагает продуктивный анализ пограничных предложений, при этом сохраняет все классические тавтологии и правила вывода и позволяет избежать «парадокса кучи». Осмислюються основні ідеї розробленої автором теорії відносної істинності для розмитих предикатів «Relative verity logic» (RVL). Теорія є спробою поєднати переваги двох протилежних підходів до проблеми розмитості (багатозначного і надоціночного). RVL пропонує продуктивний аналіз граничних речень, при цьому зберігає всі класичні тавтології і правила виведення, дозволяє уникнути «парадоксу купи».